Fernando Arrabal's "Ars Amandi": The Theme of Love in Selected Plays - Peter L. Podol (Studies in 20th & 21st Century Literature, 1977)
The evolution in Arrabal's treatment of the theme of love reflects both the development and enrichment of his dramatic techniques and the resolution of his own deep-seated psychological conflicts. Arrabal's theater utilizes his concept of dramatic ceremony to project his intense desire for personal, political and artistic liberation. Psychological and social forces combine to frustrate the fulfillment of love in his early theater (Fando and Lis, 1956) but ultimately love functions to obviate both internal and external constraints. Sexual union, which receives its most rapturous affirmation in Arrabal's plays written during the late 1960's (The Law of Barabbas, Ars Amandi, and Erotic Bestiality), reflects the reconciliation of dialectical forces present in man's psyche. Women come to serve as intermediaries between man and the world. And in the broadest sense, the dramatic structure of Arrabal's mature plays can be depicted as the movement from psychic fragmentation to psychic unity, effected by the force of love.
Keywords: Fernando Arrabal; love; theater